Throughput Performance Evaluation of LTE-Advanced with Inter-band Carrier Aggregation - Mohammed, Salim Qadir; Abdalla, Dana Salahalddin (Sulaimani Journal for Pure and Applied Sciences, 2020)
The increasing number of mobile smartphone users requires additional spectrum to maintain cellular quality of service. The 800 MHz band is a good candidate to achieve this goal. It can be used as standalone spectrum or aggregated with other licensed bands to increase the available bandwidth. This paper compares through physical layer simulation the downlink throughput versus distance performance of LTE-Advanced in two different bands. We consider a high frequency band at 2.6 GHz and the 800 MHz to model bands 7 and 20 of inter-band carrier aggregation CA_7-20 respectively. The link level simulation is performed for single antenna system at three different urban locations. The channel is modelled using an enhanced 3D ITU-R channel model combined with measured 3D radiation patterns for the base station and user equipment antennas. The BER versus SNR results show that the 800 MHz band enjoys a gain of up to 1 dB as a result of higher Ricean K-factors. Moreover, for the assumed simulation parameters, at distances beyond 400 m the throughput of the 800 MHz band is significantly higher than the 2.6 GHz band. At a distance of 750 m, the throughput for the 800 MHz band is 4.5 times greater than the 2.6 GHz band. These benefits are shown to relate to the lower path loss values observed in the 800 MHz band.
Keywords: LTE-Advanced; Carrier Aggregation; ITU; Link Level Simulation; Throughput